Perkembangan Ilmu Tasawuf Dari Klasik Hingga Modern Dan Implikasinya Terhadap Pendidikan Islam - Dzikri Yanuar Pamugka; Agus Setiawan; Rian Andrianto; Iksan Maulana; Ismail Mubarok (CV. ITTC INDONESIA, 2026)
Sufism is one of the disciplines in Islam that focuses on spiritual development, purification of the soul, and moral formation. Throughout history, Sufism has experienced significant development from the classical period to the modern era. Initially, Sufism emerged as a response to worldly tendencies and emphasized ascetic practices and devotion to God. Over time, it developed into a systematic discipline that contributed to various aspects of Muslim life, including education. This study aims to analyze the development of Sufism from the classical to modern periods and examine its implications for Islamic education. The study employs a qualitative approach using library research methods. Data were collected from books, scientific journals, and relevant academic literature. The findings reveal that Sufism has consistently played an important role in shaping Islamic values, character education, spirituality, and moral development. In the modern era, Sufism remains relevant in addressing moral degradation, spiritual crises, and psychological challenges caused by technological advancement and globalization. Therefore, the integration of Sufism into Islamic education can contribute to producing individuals who are intellectually competent, morally upright, and spiritually resilient.